Racism A short history - Fredrickson, George M (Princeton, N.J. Princeton University Press, 2002)
With a rare blend of learning, economy, and cutting insight, George Fredrickson surveys the history of Western racism from its emergence in the late Middle Ages to the present. Beginning with the medieval antisemitism that put Jews beyond the pale of hu
Keywords: Racism -- History. Race relations -- History. Race Relations -- history